The content of trace element iron is a key factor for competition between anaerobic ammonium oxidation and methane-dependent denitrification processes. (May 2018) - Lu, Yong-Ze; Fu, Liang; Li, Na; Ding, Jing; Bai, Ya-Nan; Samaras, Petros; Zeng, Raymond Jianxiong
Abstract: Coupling of anaerobic ammonium oxidation (Anammox) with denitrifying anaerobic methane oxidation (DAMO) is a sustainable pathway for nitrogen removal and reducing methane emissions from wastewater treatment processes. However, studies on the competitive relation between Anammox bacteria and DAMO bacteria are limited. Here, we investigated the effects of variations in the contents of trace element iron on Anammox and DAMO microorganisms. The short-term results indicated that optimal concentrations of iron, which obviously stimulated the activity of Amammox bacteria, DAMO bacteria and DAMO archaea, were 80, 20, and 80 μM, respectively. The activity of Amammox bacteria increased more significant than DAMO bacteria with increasing contents of trace element iron. After long-term incubation with high content of trace element iron of 160 μM in the medium, Candidatus Brocadia (Amammox bacteria) outcompeted Candidatus Methylomirabilis oxyfera (DAMO bacteria), and ANME-2d (DAMO archaea) remarkably increased in number and dominated the co-culture systems (64.5%). Meanwhile, with further addition of iron, the removal rate of ammonium and nitrate increased by 13.6 and 9.2 times, respectively, when compared with that noted in the control. As far as we know, this study is the first to explore the important role of trace element iron contents in the competition between Anammox bacteria and DAMO bacteria and further enrichment of DAMO archaea by regulating the contents of trace element iron. Highlights: Effect of trace element iron content is first investigated in Anammox-DAMO co-culture systems. Proper contents of trace element iron stimulate the activity and growth of Anammox/DAMO microbes. Anammox bacteria outcompete DAMO bacteria in the long-term experiments. Enhanced enrichment of DAMO archaea by regulating the contents of trace element iron.